Electrical Installation Training For Kelompok Karang Taruna Bencongan Indah - Yudhi Chandra Dwiaji; Nurato Nurato (Jurnal Pengabdian Barelang, 2019)
Community service activities aim to provide skills to partners regarding the installation of electricity at home or residence also provide an understanding of the dangers posed by the electricity. And it is expected that the target partners will be able to transmit their abilities to the surrounding community as well as other members of the Youth Organization (Karang Taruna) from Bencongan Indah, Tangerang. The approach method in solving existing problems is by conducting Technology Transfer Methods in the form of direct training. Implementation Activities of The Community Service Program is divided into three stages, namely preparation, implementation, and stages monitoring. Participants can take part in the activity well. It can be seen from the amount of curiosity they had about the material provided. Follow-up activities are carried out after the participants have applied some of the knowledge conveyed by the Service Team. Follow-up activities are intended to determine the impact of this activity. The activity is in the form of an obligation for participants to re-practice and understand the dangers of electricity and how to secure, read installation drawings, measure voltage, detect broken connections and can install home lighting with various switches and sockets in accordance with the requirements General Electrical Installation (PUIL). The results of the evaluations that have been conducted, it can be seen that the participants' knowledge to install lighting in the house increases and opens the mind of the participants to take advantage of the opportunities available to increase income. About 85% of participants actively responded positively to the skills and knowledge conveyed by the team.